2016
DOI: 10.1097/01.aoa.0000479527.42027.05
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Introduction of Neuraxial Labor Analgesia on Mode of Delivery at an Urban Maternity Hospital in China

Abstract: analgesic mixture did not affect the MTC needed to elicit contractions in women who received epidurally placed catheters (P = 0.731). The baseline MTC for the 1 patient who received an intrathecal catheter was 1.2 mA, but an adequate test was not determined as the MTC exceeded the protocol limit of 2 mA once the analgesic mixture was administered.This study showed that injecting a low dose of bupivacaine/fentanyl intrathecally does not impact the MTC for catheters that are placed in the epidural space, support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Because randomized controlled trials (RCTs) are often limited in terms of generalizability [8], the evidence provided by real-world observational studies can complement the findings from RCTs [9]. Previous studies on the association between labour neuraxial analgesia and adverse maternal and perinatal outcomes in China are mostly limited in single hospital with small sample sizes [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Because randomized controlled trials (RCTs) are often limited in terms of generalizability [8], the evidence provided by real-world observational studies can complement the findings from RCTs [9]. Previous studies on the association between labour neuraxial analgesia and adverse maternal and perinatal outcomes in China are mostly limited in single hospital with small sample sizes [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, implementing epidural analgesia during labor can increase vaginal birth rates as this intervention reduces women’s fear of labor pain 4 and is safe for both the mother and newborn 29,30 . In addition, a study in China showed that offering analgesia during labor reduced rated of cesarean delivery 31 . This is particularly relevant because of the public health concern and debate over the worldwide increase in cesarean deliveries, which is reflected in the rates of cesarean delivery in this survey 32,33 …”
Section: Discussionmentioning
confidence: 87%
“…It could reduce the risk of postpartum psychological disorders of women [23]. However, labor analgesia was not widely used in China [24]. Especially in general hospitals, the shortage of anesthetists renders plenty of women unable to receive the service of analgesia during childbirth [25].…”
Section: Discussionmentioning
confidence: 99%